Cracked Tooth: A Report of Two Cases and Role of Cone Beam Computed Tomography in Diagnosis - Pishipati Vinayak Kalyan Chakravarthy; Lahari Ajay Telang; Jayashri Nerali; Ajay Telang (Hindawi Limited, 2012)
Cracked tooth is a distinct type of longitudinal tooth fracture which occurs very commonly and its diagnosis can be challenging. This type of fracture tends to grow and change over time. Clinical diagnosis is difficult because the signs and symptoms are variable or nonspecific and may even resemble post-treatment disease following root canal treatment or periodontal disease. This variety and unpredictability make the cracked tooth a challenging diagnostic entity. The use of cone beam computed tomography (CBCT) in diagnosis of complex endodontic cases has been well documented in the literature. In this paper we present two cases of cracked tooth and emphasise on the timely use of cone beam computed tomography as an aid in diagnosis and as a prognostic determinant.